“THE LIFE AND COUNTRY OF THE ZIKHS, CALLED CIRCASSIANS. A REMARKABLE ACCOUNT” BY GIORGIO INTERIANO: COMMENTARIES TO THE TEXT - Druzinina, Inga Aleksandrovna; Ilusina, Milana Ur'evna; Kabardov, Inal Beslanovic (History, Archeology and Ethnography of the Caucasus, 2023)
This study explores the medieval history of the Circassians and other Northwest Caucasus peoples through a novel perspective by investigating the interactions between the Circassians of Trans-Kuban and the Mamluks of Burji (1382–1517). The primary focus is on the examination of the writings of the late 15th-century Genoese traveler Giorgio Interiano. Interiano’s observations, captured in his “Remarkable Account,” shed light on the lifestyle, customs, and appearance of the Adyghe nobility during a significant period of Circassian Mamluks’ active visits to their native lands in the Trans-Kuban region, coinciding with the reign of Sultan al-Ashraf Qaytbay (1468–1496) in Cairo. Interiano’s depictions align well with descriptions of Burji Mamluk traditions found in Arabic sources, suggesting a direct transmission of these traditions to the original carriers – Mamluks returning from the Sultanate. The article also examines the reasons behind the Circassian Mamluks’ visits to Trans-Kuban. During the analysis of Interiano’s work, texts from contemporary Arab historians of the Burji Sultanate were drawn, including al-‘Aini (d. 1451), Ibn Taghri Birdi (d. 1469), al-Sahawi (d. 1497), Ibn Shahin al-Malati (d. 1514), and Ibn Iyas (d. 1524).